Narrativas autobiográficas de estudantes: existência singular plural - (:unkn) unknown (Universidade Federal do Pampa, 2017)
If the role of Education is to aggregate knowledge and to exchange experiences, it is necessary to understand who the students in the classroom are and try to know them. Furthermore, to better known the other one must seek self-awareness, besides understanding the opposite process. In the present work, I tried to identify elements of the subjectivities, identities, memories and cultural diversity through autobiographical narratives written by the participants of the Creative Writing Workshops of Fiction and Nonfiction I have ministered at Espaço Madre Terra in Bagé. While narrating themselves, each participant wrote about the Plural-Singular Existence, a paradigm created by Marie-Christine Josso. Elements of the subjectivities that are intertwined with plurality and Cultural Diversity have emerged from the texts. The research is qualitative in nature at an exploratory level. The type of study carried out employed field research; and the texts (outputs) of the students, as well as notes recorded in field diaries, were used as instruments. The method of data analysis employed was Discursive Textual Analysis (DTA). Ten texts were analyzed; having each student produced two of them: one about the singular existence and another about the plural existence. The participants were students and workers aged 16-45. The act of reflection necessary for writing about oneself also had great importance in the process. I realized that the subjectivities composing us are contradictory and that the role of the educator, while sensitive being, must be to know how to affect and be affected, to understand the other and to realize that life histories go beyond the narratives written on paper. The multiplicity of beings-in-the-world occurs in the smallest groups. We are all different from each other. And it is this vision I sought to develop in the present work.
Keywords: Autobiografias; Identidades; Subjetividades; Memórias; Diversidade cultural; Autobiographies; Identities; Subjectivities; Memories; Cultural diversity; CNPQ::CIENCIAS HUMANAS